Dopuszczalność pozwania pracownika z państwa trzeciego przed sądem polskim na podstawie przepisów rozporządzenia nr 1215/2012 oraz kodeksu postępowania cywilnego - Torbus, Andrzej (Problemy Prawa Prywatnego Międzynarodowego, 2022)
The EU Regulation 1215/2012, as well as the Polish civil procedural law regarding individual employment relationships are employee-interest oriented. The employee’s domicile is a specific form of privilege on the level of the national jurisdiction regulations establishing international competence of national courts. The domicile provides effective protection for the employee in case of a potential dispute with an employer, who initiates the proceedings. Unfortunately, neither the Regulation 1215/2012 nor the Polish civil procedural law provides for equivalent protection for a third state employee (an employee from outside the EU) compared to an employee domiciled in Poland. The paper argues that despite a one-sided regulation, suing a third state employee before a Polish court is in principle impermissible. When applying the objective criterion to determine whether there is a national jurisdiction to hear the case, the court should consider the need to protect the employee and his or her legitimate interests. The author posits that the employee’s interest constitutes a legal basis for assessing whether in the proceedings before a Polish court — as forum conveniens — it is possible to safeguard the rights of a weaker party of a particular legal relationship. If a choice of court agreement was concluded, suing a third state employee before a Polish court will not be possible. This is because the prorogation agreement is subject to Article 23 of the Regulation 1215/2012. This provision requires that for the prorogation of jurisdiction to be effective, the employee, as party to an agreement, must be domiciled in one of the Member States.